Reading rainbow. 4 classic episodes featuring If you give a mouse a cookie [videorecording (DVD)]. - Howland, Beth; Broderick, Matthew, 1962-; Puryear, Jordan; Brady, Wayne, 1972- (Reading rainbow., 2015)
A little boy offers a mouse a cookie and a chain reaction is set in motion, illustrating how one thing leads to another.